1999
DOI: 10.1111/j.1540-8159.1999.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Discomfort Following Pectoral Defibrillator Implantation Using Conscious Sedation

Abstract: (1) Pectoral ICD implantation using conscious sedation is well tolerated. (2) Postoperative discomfort correlates with longer procedural times and larger intraoperative narcotic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Postoperative pain after cardiac device implantation has been reported to be 34 6 20 mm immediately after the procedure, decreasing to 19 6 18 mm at 1 month. 24 Postoperative pain from UAS shows a similar postoperative profile with pain a VAS of 31.6 6 19.0 mm, which decreases to 17.1 6 17.5 mm at 1 week. Compared to historical data for traditional airway reconstructive surgery for OSA, such as uvulopalatopharyngoplasty (UPPP), postoperative pain was substantially lower in severity and duration for the UAS implant procedure (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Postoperative pain after cardiac device implantation has been reported to be 34 6 20 mm immediately after the procedure, decreasing to 19 6 18 mm at 1 month. 24 Postoperative pain from UAS shows a similar postoperative profile with pain a VAS of 31.6 6 19.0 mm, which decreases to 17.1 6 17.5 mm at 1 week. Compared to historical data for traditional airway reconstructive surgery for OSA, such as uvulopalatopharyngoplasty (UPPP), postoperative pain was substantially lower in severity and duration for the UAS implant procedure (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Wound pain typically resolves on its own but oral analgesic medications can be considered postoperatively. Postoperative pain after cardiac device implantation has been reported to be 34 ± 20 mm immediately after the procedure, decreasing to 19 ± 18 mm at 1 month . Postoperative pain from UAS shows a similar postoperative profile with pain a VAS of 31.6 ± 19.0 mm, which decreases to 17.1 ± 17.5 mm at 1 week.…”
Section: Discussionmentioning
confidence: 91%
“…showed that 86% of patients who underwent subpectoral ICD implantation under conscious sedation had a mean VAS score of 34 ± 20 at 24 h after the procedure. [ 11 ] Chronic shoulder pain and disability were described in 54% of patients for more than 3 years after ICD implantation. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Using regression analysis, it was found that the use of intraoperative fentanyl and a longer time spent in the procedure were significant predictors of more intense postoperative pain. The mean VAS score for pain at one month was 19 ± 18 and 17 out of 21 patients rated this pain as "mild" [6].…”
Section: Risk Factors For Postoperative Painmentioning
confidence: 98%